1-Titanacyclobuta-2, 3-diene – an elusive four-membered cyclic allene. Issue 20 (30th April 2019) - Reiß, Fabian; Reiß, Melanie; Bresien, Jonas; Spannenberg, Anke; Jiao, Haijun; Baumann, Wolfgang; Arndt, Perdita; Beweries, Torsten
Abstract : The synthesis and characterisation of a 1-titanacyclobuta-2, 3-diene complex, an organometallic analog of elusive 1, 2-cyclobutadiene, is presented. Abstract : The synthesis of an unusual 1-metalla-2, 3-cyclobutadiene complex [ rac -(ebthi)Ti(Me3 SiC3 SiMe3 )] ( rac -ebthi = rac -1, 2-ethylene-1, 1′-bis(η 5 -tetrahydroindenyl)), a formal metallacyclic analogue of a non-existent four-membered 1, 2-cyclobutadiene, is described. By variation of the cyclopentadienyl ligand of the titanocene precursor it was possible to stabilise this highly exotic compound which selectively reacts with ketones and aldehydes to yield enynes by oxygen transfer to titanium. Analysis of the bonding and electronic structure of the metallacycle shows that the complex is best described as an unusual antiferromagnetically coupled biradicaloid system, possessing a formal Ti(iii ) centre coordinated with a monoanionic radical ligand.